2018
DOI: 10.1002/slct.201800740
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Palladium‐Alloy‐Catalyst Loaded UiO‐66‐NH2 for Reductive Amination with Nitroarenes Exhibiting High Selectivity

Abstract: AuÀPd alloy catalysts were successfully loaded into aminefunctionalized metal-organic framework (MOF, UiO-66-NH 2 ) via direct absorption/reduction method. The existence of Pd in the alloy was revealed by using in situ fourier transform infrared spectroscopy (FTIR) with CO as probe molecules. The X-ray diffraction (XRD) and transmission electron microscopy (TEM) results demonstrated the AuÀPd alloys were well dispersed within the robust UiO-66-NH 2 . AuÀPd alloy nanoparticles with low Pd content were well disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Alloying two or more different transition metals allows the catalytic activity of the MNPs to be tuned. In one of the examples, alloyed Au–Pd NPs were loaded into UiO-66-NH 2 MOF catalyst via adsorption/reduction method to obtain AuPd@UiO-66(Zr)-NH 2 and their activity was examined in the reductive amination with nitroarenes [60]. Powder XRD indicated no changes in the crystallinity of UiO-66(Zr)-NH 2 during the loading of these NPs.…”
Section: Bimetallic and Trimetallic Mnps@mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alloying two or more different transition metals allows the catalytic activity of the MNPs to be tuned. In one of the examples, alloyed Au–Pd NPs were loaded into UiO-66-NH 2 MOF catalyst via adsorption/reduction method to obtain AuPd@UiO-66(Zr)-NH 2 and their activity was examined in the reductive amination with nitroarenes [60]. Powder XRD indicated no changes in the crystallinity of UiO-66(Zr)-NH 2 during the loading of these NPs.…”
Section: Bimetallic and Trimetallic Mnps@mofsmentioning
confidence: 99%
“…TEM images and corresponding histograms of particle size distribution for as-synthesized Au-Pd 0.03 @UiO-66-NH 2 ( a , b ) and the sample after reaction ( c , d ). Reproduced with permission from [60]. …”
Section: Figurementioning
confidence: 99%
“…Liang and co-workers reported a series of catalysts for DRA, based on Au–Pd alloys well dispersed within amine functionalized metal-organic framework (MOF, UiO-66-NH 2 ) [ 115 ]. However, only Au–Pd alloy nanoparticles with low Pd content (Au-Pd 0.03 @UiO-66-NH 2 ) exhibited high selectivity for DRA with benzaldehyde and nitrobenzene, and thus the sole synthesis of N -benzylaniline in 93% yield was obtained in cyclohexane as solvent at 50 °C under 1.0 MPa of H 2 .…”
Section: Metal-catalyzed One-pot Reductive Amination Reactionmentioning
confidence: 99%
“…In the last decade, numerous other catalytic systems were developed based on supported palladium (Sydnes et al, 2008;Sreedhar et al, 2009;Dell'anna et al, 2011;Wei et al, 2013;Zhou et al, 2015;Sharma et al, 2017), platinum (Hu et al, 2011;Cirujano et al, 2013), rhodium (Huang et al, 2015), iridium Pintado-Sierra et al, 2013;Sui et al, 2017), ruthenium (Del Pozo et al, 2012), silver (Artiukha et al, 2017), and gold (Yamane et al, 2009;Artiukha et al, 2015) nanoparticles. Heterobimetallic systems such as Pd-Ag (Li et al, 2013;Chen et al, 2015), Pd-Au (Cho et al, 2018;Yin et al, 2018), Ni-Pd (Nişanci et al, 2015), and Rh-Co (Park and Chung, 2015) were also shown to be efficient catalysts for the reductive alkylation of nitro compounds. With noble metal catalysts, reductive alkylation of nitro compounds is performed under mild conditions (r.t. to 100 • C) and low hydrogen pressure (typically, 1-25 bar).…”
Section: Intermolecular Reductive Amination Of Aldehydes and Ketones mentioning
confidence: 99%